2022
DOI: 10.21037/atm-22-5438
|View full text |Cite
|
Sign up to set email alerts
|

Anlotinib suppresses lung adenocarcinoma growth via inhibiting FASN-mediated lipid metabolism

Abstract: Background: Anlotinib, a vascular endothelial growth factor receptor (VEGFR) inhibitor, has been widely used in advanced lung cancer patients, but the intrinsic mechanism of cancer cell elimination is not fully disclosed. In this study, we reported that anlotinib suppressed lung adenocarcinoma (LUAD) growth through inhibiting fatty acid synthase (FASN)-mediated lipid metabolism. Methods:To investigate the underlying mechanisms of anlotinib, an A549 cell line-derived xenograft model was constructed and a proteo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…Targeting lipid metabolism has become an attractive choice for cancer treatment [ 30 ]. Emerging evidence has determined that many molecules exhibit therapeutic potential against LUAD through inhibiting lipid metabolism, such as Anlotinib (a vascular endothelial growth factor receptor inhibitor) [ 31 ] and endothelial lipase gene [ 32 ]. To combine with our findings, we speculated that the inhibition of lipid metabolism may contribute to the role of CD147 silencing in inhibiting LUAD.…”
Section: Discussionmentioning
confidence: 99%
“…Targeting lipid metabolism has become an attractive choice for cancer treatment [ 30 ]. Emerging evidence has determined that many molecules exhibit therapeutic potential against LUAD through inhibiting lipid metabolism, such as Anlotinib (a vascular endothelial growth factor receptor inhibitor) [ 31 ] and endothelial lipase gene [ 32 ]. To combine with our findings, we speculated that the inhibition of lipid metabolism may contribute to the role of CD147 silencing in inhibiting LUAD.…”
Section: Discussionmentioning
confidence: 99%
“…Related drugs could act on the FAM process in LUAD. For example, anlotinib controls LUAD progression through inhibiting FASN-mediated FAM ( Shen et al, 2022 ). Chaoyang Liang et al also showed that the overexpression of genes related to FAM enzymes (ACOT11) regulates the growth, differentiation, and metastasis of LUAD cells through a variety of signaling pathways ( Liang et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%